Hubungan Kadar Gula Darah Terhadap Gambaran Funduskopi Pasien Retinopati Diabetik Operable Dan Non Operable Di Rumah Sakit Prima Vision Tahun 2023-2025 - Rahmah, Ratu Aulia; Fadillah, Qori; Pratama, Irza Haicha (Syntax Corporation, 2025)
This study aims to determine the effect of Channa striata extract on Malondialdehyde (MDA) levels and the histopathological features of the heart in liver cirrhosis model rats. This experimental research used a randomized post-test only control group design with male Wistar rats (Rattus norvegicus) as test subjects. Liver cirrhosis was induced using carbon tetrachloride (CCl₄) for six weeks. The rats were divided into control and treatment groups, each receiving different doses of Channa striata extract. The observed parameters included cardiac MDA levels as an indicator of oxidative stress and histopathological changes in heart tissue examined using hematoxylin-eosin (HE) staining. The results showed that Channa striata extract significantly reduced MDA levels compared to the control group and improved the histological structure of the heart in cirrhosis model rats. These findings indicate that Channa striata possesses hepatocardioprotective potential through antioxidant mechanisms that can reduce tissue damage caused by oxidative stress.